Compute the double integral:
∫ 1 e ∫ − 2 2 y + e x y x 2 ln ( y ) d x d y
If this integral evaluates to b a , where a and b are positive coprime integers, enter a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given double integral after some rearrangement is:
I = ∫ 1 e ∫ − 2 2 ( 1 + e x x 2 ) ( y ln ( y ) ) d x d y
Now, since the limits of integration are constant, the integral can be rewritten as:
I = ( ∫ 1 e y ln ( y ) d y ) ( ∫ − 2 2 1 + e x x 2 d x ) = I 1 I 2
I 1 = ∫ 1 e y ln ( y ) d y
Taking ln ( y ) = z transforms the integral to:
I 1 = ∫ 0 1 z d z = 2 1
Now:
I 2 = ∫ − 2 2 1 + e x x 2 d x = ∫ − 2 2 1 + e − x x 2 d x
Therefore:
2 I 2 = ∫ − 2 2 x 2 d x ⟹ I 2 = 3 8
Finally:
I = I 1 I 2 = 3 4
Note:
If a , b , c and d are constants, then:
J = ∫ a b ∫ c d f ( x ) g ( y ) d x d y = ( ∫ a b g ( y ) d y ) ( ∫ c d f ( x ) d x )
Why are those integrals fromthe first time you mention I2 equal?
Log in to reply
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 1 e ∫ − 2 2 y + e x y x 2 ln y d x d y = ∫ 1 e y ln y ∫ − 2 2 1 + e x x 2 d x d y = ∫ 1 e y ln y ∫ 0 2 x 2 d x d y = 3 8 ∫ 1 e y ln y d y = 3 8 ( ln 2 y ∣ ∣ ∣ ∣ 1 e − ∫ 1 e y ln y d y ) = 3 8 × 2 1 [ ln 2 y ] 1 e = 3 8 × 2 1 = 3 4 See proof: ∫ − a a 1 + c g ( x ) f ( x ) d x = ∫ 0 a f ( x ) d x where f ( x ) is even and g ( x ) odd. By integration by parts Note that ∫ 1 e y ln y d y = ln 2 y ∣ ∣ ∣ ∣ 1 e − ∫ 1 e y ln y d y
Therefore, a + b = 4 + 3 = 7 .
Proof for ∫ − a a 1 + c g ( x ) f ( x ) d x = ∫ 0 a f ( x ) d x for even f ( x ) and odd g ( x ) .